Mental Health Outcomes Amongst Health Care Workers During COVID 19 Pandemic in Saudi Arabia - Al Ammari, Maha; Sultana, Khizra; Thomas, Abin; Al Swaidan, Lolowa; Al Harthi, Nouf (Frontiers in Psychiatry, 2021)
Objectives: The study aimed to assess the mental health outcomes and associated factors among health care workers during COVID 19 in Saudi Arabia. Design, Setting, and participants: We conducted a cross-sectional survey of health care workers from tertiary care and ministry of health Centres across the central, eastern, and western regions of Saudi Arabia. There were 1150 participants in the survey, and we collected demographic and mental health measurements from the participants. Primary outcomes and Measures: The magnitude of symptoms of depression, anxiety, and insomnia was measured using the original version of 9- item patient health questionnaire (PHQ-9), the 7- item generalized anxiety disorder scale (GAD-7), and 7- item insomnia severity index (ISI). We use the multiple logistic regression analysis to identify the associated risk factors of individual outcomes. Results: The scores on the PHQ-9 showed that the largest proportion of health care workers (76.93%) experienced only normal to mild depression (50.83 % and 26.1%, respectively). The scores on the GAD-7 showed that the largest proportion of health care workers (78.88%) experienced minimal to mild anxiety (50.41% and 28.47%, respectively). The scores on the ISI showed that the largest proportion of health care workers (85.83%) experienced absence to subthreshold insomnia (57.08% and 28.75%, respectively). The risk factors for depression in health care workers were Saudi, living with family, working from an isolated room at home, and frontline workers. For anxiety, being female was a risk factor and for insomnia, a frontline worker was a risk factor. Conclusion: It was observed that the symptoms of depression, anxiety, and insomnia were reported in a lower proportion of Health care workers in our study. The participants who were female, frontline workers, Saudi, living with family, and working from home in isolated rooms were predisposed to developing psychological disorders.